The Nexus between Trade, Financial Development, Remittances and Economic Growth: A Vector Autoregression Approach - Maune, Alexander (Acta Universitatis Danubius. Œconomica, 2024)
This study examines the nexus between trade, financial development, remittances and economic growth in Zimbabwe using time-series data collected from the World Bank Worldwide Development Indicators database from 1980 to 2022. Vector autoregression models were estimated using Stata/SE 14.2 to analyse “short-run” relationships among the four variables. The results obtained showed the non-existence of cointegration equations in the series. The significant findings are the positive "short-run" causal effects of first lag GDP regressor on GDP at 0.05%, first lag remittances regressor on GDP, first lag financial development regressor on financial development, and first lag trade and remittances regressors on remittances, at 0.01% level of significance. Moreover, the Granger causality test showed that the remittances Granger causes GDP and trade Granger causes remittances in the "short-run", while the opposite is true for other variables. This study is essential to researchers and policymakers. It is recommended that the government formulate policies that promote the inflow of remittances, trade, and financial development for meaningful economic growth.